629 Targeting a shared TP53 neoantigen with bispecific T cell retargeting antibody. (10th December 2020) - Hsiue, Emily; Wright, Katharine; Douglass, Jacqueline; Hwang, Michael; Mog, Brian; Pearlman, Alexander; Schaefer, Annika; Aitana Azurmendi, P; Wang, Qing; Pardoll, Drew; Papadopoulos, Nickolas; Kinzler, Kenneth; et al.
Abstract : Background: TP53 is the most commonly mutated cancer driver gene but drugs that target TP53 are not yet available. A peptide derived from the most common p53 mutation R175H (HMTEVVRHC) can be presented by a common human leukocyte antigen (HLA-A*02:01) after proteasomal degradation. 1 We aimed to develop T cell receptor (TCR)-mimic antibody targeting this shared neoantigen. Methods: We constructed a single-chain variable fragment (scFv) phage display library that presents scFvs at an estimated diversity of 3.6e10. Mutant peptide-HLA (pHLA)-specific scFvs were enriched through five rounds of positive and negative selections. Mutant pHLA-specific scFv clones were converted into bispecific T cell retargeting antibodies in the single-chain diabody (scDb) format by linking with the anti-CD3 scFv UCHT1. 2 These scDbs were tested in T cell co-culturs in the presence of target pulsed cells or target cells that either overexpress the p53 neoantigen or present the p53 neoantigen at endogenous levels. In vivo efficacy was assessed by administering scDb in NSG xenograft mouse model. The structural basis of the binding specificity was evaluated by X-ray crystallography. Results: We identified an scFv, termed clone H2, that specifically binds p53 R175H/HLA-A*02:01 pHLA and not its wild-type counterpart at a Kd of 86 nM (figure 1A). H2-scDb induced T cell cytokine release and cytotoxicity in the presence of 1) HLA-A*02:01-expressing cells pulsed with the p53R175H peptide, 2) cells transfected with HLA-A*02:01 and p53 R175H, and 3) cancer cell lines KMS26, KLE, and TYK-nu that express endogenous HLA-A*02:01/p53 R175H (figure 1B-E). T cell activation was diminished when TP53 was knocked out from these cancer cell lines using CRISPR (figure 1E). When administered to NOD scid gamma (NSG) mice systemically engrafted with the KMS-26 cell line, H2-scDb significantly suppressed tumor growth (figure 1 F, G). The structure of p53 R175H/HLA-A2 bound to the H2-Fab fragment shows that four complementarity-determining region loops of the H2 antibody formed a cage-like configuration around the C-terminus of the p53 R175H peptide, trapping the mutant histidine (His175) and the adjacent arginine (Arg174) residues in a stable interaction, which provides the structural basis for the specificity (figure 2). Conclusions: We have developed a TCR-mimic bispecific T cell engager H2-scDb that recognized the shared neoantigen HLA-A*02:01/p53 R175H pHLA complex with exquisite specificity. It effectively activated T cells and lysed tumor cells both in vitro and in vivo. This approach could in theory be used to target cancers containing mutations that are difficult to target in conventional ways. Acknowledgements: We thank Surojit Sur, Nicolas Wyhs, Ashley Cook, Marco Dal Molin, Richard L. Blosser, Lilian Dasko-Vincent, Christopher Thoburn, Jianhong Cao, and José Rodríguez Molina for assistance with this study. Trial Registration: NA Ethics Approval: NA Consent: NA References: Lo W, Parkhurst M, Robbins PF, Tran E, Lu YC, Jia L, Gartner JJ, Pasetto A, Deniger D, Malekzadeh P, Shelton TE, Prickett T, Ray S, Kivitz S, Paria BC, Kriley I, Schrump DS, Rosenberg SA. Immunologic recognition of a shared p53 mutated neoantigen in a patient with metastatic colorectal cancer. Cancer Immunol. Res 2019;7 :534–543. Stork R, Campigna E, Robert B, Muller D, Kontermann RE. Biodistribution of a bispecific single-chain diabody and its half-life extended derivatives. J Biol Chem 2009;284 :25612–25619